Collaborative open bibliographic network for Malaysian school libraries - Raja Ismail, Nik Roslina; Mansor, Yushiana; Awang Abu Bakar, Normi Sham (2012)
Collaborative bibliographic network among libraries has long gained its popularity not only due to the sheer cost of integrated library systems (ILS) but also the many benefits gained from being a member of library network or consortium. The emerging trend of the use of open source ILS in consortia has already marked successful results including among school libraries. Among the prominent ones is the development of virtual union catalog which not only promotes resource sharing, but also has great potentials in making school resource centres (SRC) online catalogues as a tool for information resource discovery. The paper will specifically explore the feasibility of building such network within school resource centers in Malaysia. The awareness, benefits and issues like interoperability will also be discussed. This paper will discover the potential of setting up a collaborative bibliographic network among SRC in Malaysia by deploying open source ILS. A general framework in setting up SRC bibliographic network in Malaysia will be proposed with focus on the creation of compatible library catalog that could support the distributed environment and Z39.50 protocol. Popular ILS such as Koha, OPALS, and Evergreen will be presented and their applications in library network will be appraised in light of Malaysian SRC environment. Finally, the paper will propose potential research areas that would position and enhance the role of school resource centres in producing life-long learners and bridging the digital divide through the deployment of open source ILS in Malaysian SRC.